THE EFFECT OF LIQUIDITY, COMPANY SIZE, AND ASSET STRUCTURE ON STRUCTURE TRADING COMPANY CAPITAL IN THE IDX - Sri Laksmi Pardanawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This his research is to see how liquidity, company scale, and asset composition affect trading companies' capital structures on the Indonesia Stock Exchange. In this sample, the population consisted of 61 trading companies that were listed on the IDX. Purposive sampling was used, and a total of 27 trading firms were found. The financial statements of trading firms listed on the IDX are included in this analysis as secondary evidence The multiple linear regression test was used to analyze the results. The liquidity variable has a substantial impact on capital structure, according to the findings. The capital structure is unaffected by the company scale aspect Capital structure is influenced by the asset structure vector. The capital structure is influenced by liquidity factors, company scale, and asset structure all at the same time. The three variables had a 65.2 percent impact on the capital structure, as seen by the magnitude of Adjusted R2 0.652, while the remaining 34.8 percent was affected by variables other than those used in this analysis. Keywords: Capital Structure, Liquidity, Firm Size, Asset Structure, IDX